Workshop Literasi TIK & Pengembangan Media Pembelajaran Berbasis TIK Untuk Meningkatkan Profesionalisme Guru SD Di Kota Parepare - Krismanto, Wawan (International Journal of Community Service Learning, 2018)
The purpose of community service is to provide knowledge and skills to elementary school teachers about: 1) ICT Literation, 2) the use of ICT for learning, and 3) techniques to develop ICT-based learning media. To equip the ability, the method applied is a 2-day workshop equivalent to 16 hours lesson (JP). This dedication program has been implemented and followed by 22 teachers from 7 public elementary schools in Parepare Town of South Sulawesi. Based on the process evaluation data, 64% of the participants rated very well against the workshop. The usefulness of this workshop was also felt very well by 36% of the participants. In the material element 82% of participants stated good, on the element of facilitator 64% of participants rated very well and on time allocation element 50% of participants assume less. The results of the workshops appear to be observed ie the participants have been able to: 1) explore the use of the internet to support the implementation of learning, such as youtube, learning sites, virtual laboratories, 2) to create effective presentations and interactive learning media using powerpoint; 3) develop video-based learning media animation simple utilizing animaker application and 4) developing learning evaluation tool with wondershare quiz creator.Keywords: ICT Literacy, media development